PELAKSANAAN PEMBELAJARAN TAHFIZ AL-QUR’AN SISWA KELAS 8 MTSS MUHAMMADIYAH LAWANG TIGO BALAI KEC. MATUR, KAB. AGAM - Dewi Ana Kartika; Salmiwati Salmiwati; Wedra Aprison; Arman Husni (KOLONI, 2022)
The background of the research is because learning tahfiz Al-Qur'an is a subject that has just been included in local content lessons at MTsS Muhammadiyah Lawang Tigo Balai. in the midst of the COVID-19 pandemic, due to unfavorable circumstances and limited face-to-face learning time. This research is in the form of a qualitative field research. Data collection techniques that the authors use in this study are interviews and documentation. In the implementation of tahfiz Al-Qur'an learning in grade 8 MTsS Muhammadiyah Lawang Tigo Balai, the teacher uses two learning methods namely the Kitabah method and the Tasmi method, the teacher uses the Kitabah method when learning online, while the Tasmi method is used when face-to-face learning in school. Obstacles encountered by the teacher in applying the book method include some students who are less careful in recording the verse material to be memorized. When viewed from the side of students, there are several obstacles that students feel in memorizing the Qur'an. Among them are difficulties in memorizing verses that are too long, and sometimes students feel lazy in memorizing the Qur'an. The inhibiting factors in learning tahfiz are that some students are lazy to memorize, the lack of support that children get from parents at home, and the allocation of face-to-face learning time is reduced to 40 minutes, causing the implementation of Tahfiz Al-Qur'an learning to be less effective.  Keyword: Implementation of Tahfiz Learning, Methods, Constraints/Inhibiting Factors.